THE IMPACT OF SELF-EFFICACY, LEARNING MOTIVATION, AND PROCRASTINATION ON ACADEMIC ACHIEVEMENT OF STUDENTS FACULTY OF ECONOMICS, JAKARTA STATE UNIVERSITY - Tuty Sariwulan; Fera Pujiastuti (Jurnal Ilmiah Econosains, 2019)
The purpose of this study was to determine the impact of self-efficacy, learning motivation, and procrastination on the academic achievements of the Faculty of Economics, Jakarta State University. This study uses the ex post facto method with a causal approach and analyzed by a path analysis model using 135 respondents. The results of this study indicate that there are positive effects of self-efficacy and learning motivation, and the negative impact of procrastination together has a significant impact on academic achievement.